2012
DOI: 10.1093/hmg/dds425
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of genome-wide association studies to identify prostate cancer susceptibility loci associated with aggressive and non-aggressive disease

Abstract: Genome-wide association studies (GWAS) have identified multiple common genetic variants associated with an increased risk of prostate cancer (PrCa), but these explain less than one-third of the heritability. To identify further susceptibility alleles, we conducted a meta-analysis of four GWAS including 5953 cases of aggressive PrCa and 11 463 controls (men without PrCa). We computed association tests for approximately 2.6 million SNPs and followed up the most significant SNPs by genotyping 49 121 samples in 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
96
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 17 publications
2
96
0
Order By: Relevance
“…Although the definition of aggressive PCa has differed across studies (5-8), the Gleason grading system remains the most powerful prognostic predictors for this cancer more than 40 years after its inception and nearly 10 years after its last update because it delineates the architectural patterns of tumors (9). GS is the core value in risk-scoring systems, including the D'Amico classification system (10), which incorporates the GS, clinical stage, and PSA level to stratify the risk of recurrence of localized PCa before treatment and is used to guide treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the definition of aggressive PCa has differed across studies (5-8), the Gleason grading system remains the most powerful prognostic predictors for this cancer more than 40 years after its inception and nearly 10 years after its last update because it delineates the architectural patterns of tumors (9). GS is the core value in risk-scoring systems, including the D'Amico classification system (10), which incorporates the GS, clinical stage, and PSA level to stratify the risk of recurrence of localized PCa before treatment and is used to guide treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses of GWAS have yielded the identification of nearly 100 risk loci for PC, which together account for approximately one-third of the heritable risk for PC development [42,43]. Yet, the search for SNPs associated with aggressive disease development has proven more challenging, and very little overlap has been observed between loci associated with susceptibility to PC development and loci that differentiate aggressive from non-aggressive PC [43,44]. Identification of aggressive disease loci is of clinical importance since they could potentially aid in the stratification of patient risk in fatal forms of PC.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of aggressive disease loci is of clinical importance since they could potentially aid in the stratification of patient risk in fatal forms of PC. However, detection of these loci in GWAS are hindered by small cohort sizes and the stringent conditions required to correct for multiple testing [44,45], where positive associations that do not satisfy these conditions may be discarded as false. With respect to our use of a human PC GWAS, we acknowledge that the sample size in the CGEMS GWAS PC cohort is relatively small, and replication of the findings here in larger cohorts is of importance.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent GWA studies showed that some of these risk variants may correlate with the progression of prostate cancer [1419] and, thus, could be clinically useful given that the majority prostate cancer cases are indolent and not a threat to life. Individually, the identified risk variants are low-penetrance susceptibility loci and have little clinical utility.…”
Section: Introductionmentioning
confidence: 99%